Najazdy wikingów a kryzys Kościoła anglosaskiego w IX wieku. Zarys problemu - Zinkiewicz, Jacek (Analecta Cracoviensia, 2008)
The end of the 7th and the first half of the 8th century was a time of flowering and relatively greateness of anglo-saxon Church. Nonetheless some prominent ecclesiastics (Bede Venerable for example) caught sight of the crisis symptoms. Any attempts of more or less general reforms of the Church, which had place since the Clofesho Council (747), had been unsuccessful. Political disruption and frictions between rulers and bishops made impossible any real and constant changes. Secularised minsters were too serious sources of mundane profits for their lay masters, and that’s why they didn’t want to leave the control of this issue to the clergymen. It caused fall of discipline, morality and intelectual quality of minsters. The end of the 8th and the beginning of the 9th centuries gave another examples of unsuccessful attempts to reform the basic problems of anglo-saxon Church in the time of political confusion. There also appeared another factor, which soon radically influenced political, social, cultural and ecclesiastical situation of anglo-saxon kingdoms.Since the end of the 8th century the Viking raids era had begun. The viking menace didn’t seem very considerable at first, it happended after some time when started to be regular. In the first half of the 9th century there existed some ecclesiastical centres, still giving an example of greateness, which could have been the source of potential reform. But to do this, a social and political peace was needed, and also cooperation of two powers: lay and spiritual. An attempts of the Church reforms (or rather - minsters), initiated by archibishop Wulfred, failed, and the next had place during the reign of Alfred the Great. In the meantime the viking menace grew up. The vikings caused very serious impoverishment of the Church in Britain, and also shaked its structures. They caused a great material losses but did not start ecclesiastical crisis; a symptoms of this crisis had been seen long before the Vikings, as a result of gradual fall and because of unrealized changes suggested since the times of Bede, and especially since the Clofesho Council in 747. In this circumstances, in the moment of the highest exterior menace, there couldn’t have been a place for any contentions, and Alfred the Great kept in his hands an initiative of the general renewal and reforms, also by means of foreign clergy.